2022
DOI: 10.3201/eid2811.220542
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Histoplasmosis among Persons with Advanced HIV Disease, Nigeria

Abstract: H istoplasmosis, an invasive fungal infection endemic in the Americas, Africa, and Asia, with a few cases reported among immigrants to Europe, was classified as an AIDS-defining disease in 1987 (1,2). Incidence of disseminated histoplasmosis is 5%-25% in persons with advanced HIV disease (AHD; World Health Organization [WHO]-preferred term for AIDS), and according to recent data from South America, mortality rates are similar to those for tuberculosis among this patient group (3,4). In Latin America, high prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…It is thus not surprising that despite the increasing cases of DH, GIH is rarely reported. Underreporting is surprisingly pronounced in Africa, a region known to have documented several cases of DH [ 4 , 6 , 125 , 126 , 127 ]. An extensive review on histoplasmosis in Africa that spanned seven decades identified 470 cases of histoplasmosis, of which only one case was reported with GIH [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thus not surprising that despite the increasing cases of DH, GIH is rarely reported. Underreporting is surprisingly pronounced in Africa, a region known to have documented several cases of DH [ 4 , 6 , 125 , 126 , 127 ]. An extensive review on histoplasmosis in Africa that spanned seven decades identified 470 cases of histoplasmosis, of which only one case was reported with GIH [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…An extensive review on histoplasmosis in Africa that spanned seven decades identified 470 cases of histoplasmosis, of which only one case was reported with GIH [ 5 ]. The paucity of data on GIH is first and foremost probably because histoplasmosis is still a neglected fungal disease in most parts of Africa, although with recent epidemiological studies, awareness is improving [ 125 , 126 , 127 ]. Recognition and reporting of GIH may also be hampered by a lack of adequate diagnostic procedures such as colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational risk factors identified to be associated with histoplasmosis in AIDS-patients were working with birds [35] or history of exposure to chicken coops [40]. Among case patients who had worked with soil contaminated with chicken or bat droppings and who could recall the date of their most recent exposure, the median time from their last exposure to the onset of symptoms was of 1.6 years [35].…”
Section: Epidemiologymentioning
confidence: 99%
“…Several risk factors are associated with the progressive disseminated form: low CD4 lymphocytes count (less than 150) and low nadir CD4 count [40,42], low CD8 count [42], history of chronic medical condition and history of herpes simplex infection [35], and male gender [42]. Receiving treatment with TMP-SMZ was associated with a decreased risk of poor outcomes [35].…”
Section: Epidemiologymentioning
confidence: 99%
“…Pulmonary involvement is the most common form, since it is the site of primary infection. Disseminated forms are mainly described in immunocompromised subjects [ 2 , 7 , 8 ]. Natural reservoirs of conidia include bat guanos and bird droppings [ 9 ].…”
Section: Introductionmentioning
confidence: 99%